2019
DOI: 10.3389/fnins.2018.00993
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Dynamic FDG-PET for Detecting Epileptic Foci and Analyzing Reduced Glucose Phosphorylation in Refractory Epilepsy

Abstract: Aims: Static fluorodeoxyglucose (FDG)-positron emission tomographic (PET) imaging plays an important role in the localization of epileptic foci. Dynamic FDG PET allows calculation of kinetic parameters. The aim of this study was to investigate whether kinetic parameters have potential for identifying epileptic foci, and to assess the correlation of parameters asymmetry indexes (ASYM) between dynamic and static FDG PET for understanding the pathophysiology of hypometabolism within intractable epilepsy.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…FDG-PET imaging plays an important role in the localization of epileptic foci. Tang et al performed an investigation on kinetic parameters for epileptic foci identification (24). They assessed the correlation of parameters asymmetry indexes (ASYM) between dynamic and static FDG-PET to understand the hypo metabolism pathophysiology within intractable epilepsy.…”
Section: Utility Of Fdg-pet In the Identification Of The Epileptogenic Zonementioning
confidence: 99%
“…FDG-PET imaging plays an important role in the localization of epileptic foci. Tang et al performed an investigation on kinetic parameters for epileptic foci identification (24). They assessed the correlation of parameters asymmetry indexes (ASYM) between dynamic and static FDG-PET to understand the hypo metabolism pathophysiology within intractable epilepsy.…”
Section: Utility Of Fdg-pet In the Identification Of The Epileptogenic Zonementioning
confidence: 99%
“…FDG was injected intravenously at a mean dose of 148 MBq. Images were acquired in three dimensions over a 60 min time period, following scanning protocol described by Tang et al (11). Image processing was performed using the SPM12 (Wellcome Department of Cognitive Neurology, London, UK).…”
Section: Fdg-pet Image Acquisition and Processingmentioning
confidence: 99%
“…While recurrent seizures following surgery suggested that some epileptogenic tissue distinct from the primary temporal lobe epileptogenic zone has not been resected, and those areas might reflect dual pathology beyond seizure onset zone, but usually negative in magnetic resonance imaging (MRI) or impossibility of whole brain electrocorticogram (ECoG) coverage (5,7), thus posing a difficult diagnostic challenge. Emerging evidence suggests that temporal lobe hypometabolism on fluorine-18-fluorodeoxyglucose positron emission tomography (FDG-PET) can provide relevant information on the epileptogenic zone extent and surgical outcome (9)(10)(11). The highest clinical benefit of FDG-PET can be achieved in patients with MRI-negative TLE (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients show no structural lesions on MRI or discordant findings between MRI and EEG. Thus, aberrant brain function needs to be assessed using other noninvasive imaging modalities such as MEG, Single Photon Emission Computed Tomography (SPECT), and PET [18,[21][22][23]. Interictal 18 F-FDG PET scans contribute to the functional deficit zone definition by Fig.…”
Section: Hybrid Pet/mri Showed Advantage In Soz Precise Localizationmentioning
confidence: 99%